KARAKTERISTIK BAHASA INDONESIA ORANG MINANGKABAU - Rona Almos; Reniwati Reniwati; Noviatri Noviatri (Sunan Kalijaga State Islamic University Yogyakarta, 2013)
The Indonesian is multi spoken languages society. Besides speaking with the official language (bahasa Indonesia), they also speaking in their own mother language. The use of local languages or the mother tongue is preferably as second language. Therefore, the acquisition of Indonesian, especially for Minangkabau society is strongly influenced by the structure of the first language. This is called as dialect or style. Slang or style can be seen from the lingual units that used by the speakers of the language. Lingual unit is a unit of language that carries meaning, both lexical and grammatical meaning. Unit lingual include morphemes, words, phrases, clauses, sentences, and discourse. In addition, there is another element which is the smallest unit in the language, segmental elements (phonemes) and supra-segmental elements (intonation). The results of the data analysis showed that there are some unit lingual speech marking Indonesian Minang people, namely: elements of segmental and supra-segmental elements, phatic, and sentence structure. In term of segmental elements, I have found six phonemes in Minangkabau language that affects Indonesian, phonemes are: /e/, /p/, /s/, /k/, and /j/. Moreover, in supra-segmental elements it appears that there tends to tone up the filler constituent predicate function. In declarative sentences, tone up there on the last syllable. In interrogative sentences, tone up tens to present in interrogative qualifiers. In imperative sentences, the intonation rising filler constituents tend be found in the predicate function, especially on the final syllable.